2015
DOI: 10.1111/cobi.12535
|View full text |Cite
|
Sign up to set email alerts
|

On how much biodiversity is covered in Europe by national protected areas and by the Natura 2000 network: insights from terrestrial vertebrates

Abstract: The European Union has made extensive biodiversity conservation efforts with the Habitats and Birds Directives and with the establishment of the Natura 2000 network of protected areas, one of the largest networks of conservation areas worldwide. We performed a gap analysis of the entire Natura 2000 system plus national protected areas and all terrestrial vertebrates (freshwater fish excluded). We also evaluated the level of connectivity of both systems, providing therefore a first estimate of the functionality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 41 publications
2
85
0
Order By: Relevance
“…Revealing the patterns that impact the efficiency of PAs networks for biodiversity conservation, our results can inform management decisions and influence the prioritization of conservation efforts. This is especially important given that the future PAs networks will likely face fragmentation problems due to the increase in the proportion of smaller PAs (Maiorano et al, 2015; Meyer, Beard & Cronan, 2015) and urban expansion around PAs (Bonet-García et al, 2015; Martinuzzi et al, 2015; Wood et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Revealing the patterns that impact the efficiency of PAs networks for biodiversity conservation, our results can inform management decisions and influence the prioritization of conservation efforts. This is especially important given that the future PAs networks will likely face fragmentation problems due to the increase in the proportion of smaller PAs (Maiorano et al, 2015; Meyer, Beard & Cronan, 2015) and urban expansion around PAs (Bonet-García et al, 2015; Martinuzzi et al, 2015; Wood et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…While the scientific community has carefully studied the effectiveness of the Natura 2000 network in terms of whether the SACs and SPAs contain various taxonomic groups and their habitats (e.g. Abellán and Sánchez-Fernández, 2015;Lisón et al, 2013Lisón et al, , 2015bMaiorano et al, 2015;Sánchez-Fernández et al, 2008), very little attention has been paid to whether the SDFs supporting these protected areas accurately represent the biodiversity known to be within them. This issue is very important because the SDFs underpin management and conservation plans, and are central to the practical implementation of sustainable development (Popescu et al, 2014): conservation planning should be established in accordance with actual biodiversity patterns (Pressey et al, 2003;Jeanmougin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have evaluated the effectiveness of the N2000 network in representing particular taxonomic groups, including plants (Chiarucci et al, 2008;Kallimanis et al, 2014), invertebrates (Abellán et al, 2007Sánchez-Fernández et al, 2008) and various vertebrate groups (Abellán and Sánchez-Fernández, 2015;Albuquerque et al, 2013;Lisón et al, 2015b;Maiorano et al, 2015). Some have examined species of conservation concern in different taxonomic groups, for example species included in Annex II of the Habitats Directive (Gruber et al, 2012;Lisón et al, 2013) or threatened species (Trochet and Schmeller, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most comprehensive assessment so far is the one of Maiorano et al (2015), who performed a gap analysis of the entire Natura 2000 system as well as national protected areas for all terrestrial vertebrates. Their results suggested that, at a continental level, the Natura 2000 network acts as a good complement to existing national protected areas.…”
Section: Figure 1-1 the Natura 2000 Network For The Eu-28 Which Compmentioning
confidence: 99%